2016
DOI: 10.15244/pjoes/61261
|View full text |Cite
|
Sign up to set email alerts
|

Land Use Regression Models Using Satellite Aerosol Optical Depth Observations and 3D Building Data from the Central Cities of Liaoning Province, China

Abstract: Land use regression (LUR) modeling is a promising method for assessing the spatial variation of air pollutant concentrations. We developed an LUR model for air pollutants (SO 2 , NO 2 , and PM 10 ) in the central cities of Liaoning Province using monitoring data collected during 2013. We evaluated whether the addition of annual satellite aerosol optical depth (AOD) observations and fi ve canyon indicators (building height, building coverage ratio, fl oor area ratio, building shape coeffi cient, and high-rise b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Since then LUR along with geographic weighted regression (GWR) models have been used as a computationally cost-effective method for mapping primary and secondary formed pollutants to explain spatio-temporal variation in the concentrations due to geographic factors. Recently interest is surging to develop LUR models for PM 2.5 [9][10][11][12][13] due to the cognizance of its effect on human health [14] and its rising concentration across developing countries [15]. Van Donkelaar et al [16] showed that using land-use in GWR to observed and simulated AOD and ambient PM 2.5 concentrations results in significant PM 2.5 concentration prediction in locations lacking ground observations.…”
Section: Introductionmentioning
confidence: 99%
“…Since then LUR along with geographic weighted regression (GWR) models have been used as a computationally cost-effective method for mapping primary and secondary formed pollutants to explain spatio-temporal variation in the concentrations due to geographic factors. Recently interest is surging to develop LUR models for PM 2.5 [9][10][11][12][13] due to the cognizance of its effect on human health [14] and its rising concentration across developing countries [15]. Van Donkelaar et al [16] showed that using land-use in GWR to observed and simulated AOD and ambient PM 2.5 concentrations results in significant PM 2.5 concentration prediction in locations lacking ground observations.…”
Section: Introductionmentioning
confidence: 99%
“…2 presents the final AOD distribution. In this study, we used AOD data as an environment indicator, as it has been proven to accurately reflect air quality [21][22][23]. The AOD value of the southeast region of the study area is obviously higher than that of the northwest region, likely due to their different regional landforms.…”
Section: Resultsmentioning
confidence: 99%
“…Example datasets are NO 2 vertical column density (VCD) from the Ozone Monitoring Instrument, and aerosol optical depth (AOD) for PM [63]. As with studies in Europe [64][65][66][67][68], studies in China have reported that incorporating satellite-based estimates improved model performance of regional LUR models for NO 2 , PM 10 , and PM 2.5 [41,56]. More temporally-resolved models have also been reported; for example, using satellite AOD and VCDs, linear mixed-effects LUR models have been used to estimate daily average concentration of PM 10 [53] and NO 2 [51].…”
Section: Data Availability/accessibility Challengesmentioning
confidence: 99%
“…The pixel sizes of current instruments are around several hundred km 2 [70]; and thirdly, the availability of some satellite data are subject to meteorological conditions; for example, cloud cover can influence the quality of the retrievals of many variables (e.g., AOD) that are sensitive to atmospheric optics. In addition, satellite data can have systematic seasonal errors [41,56]. For example, Yang et al [41] reported that satellite remote sensing tended to overestimate concentrations of PM 2.5 in summer and underestimate in winter.…”
Section: Data Availability/accessibility Challengesmentioning
confidence: 99%